National Victories and Barbarism in Modern Greece: Re-enacting the Battle of Salamis in the 1960s - Balaskas, Vasileios (Coimbra University Press, 2024)
The Greek victory at the battle of Salamis has acquired a symbolic significance in modern Greek national discourse. In the post-war period (1950-1974), commemorative ceremonies of the battle exalted the glory of the Greek military past and turned Salamis into a representation of the combative virtues of the nation. When a dictatorial regime came in power in 1967, it imposed its militaristic identity by re-appropriating and re-enacting the battle of Salamis as a patriotic symbol of martial victories. As these events were held within the anti-communist discourse of ethnikofrosyni (national-mindedness), they propagated a nationalist rhetoric that distinguished a civilized self from communist barbarism.
Keywords: Batalla de Salamina, 480 a.C; Recreaciones históricas - Grecia; Battle of Salamis; Ethnikofrosyni; Greek communism; Classical reception